Peningkatan Hasil Belajar Matematika melalui Problem Based Learning (PBL) Berbantu Media Kartu Bergambar pada Kelas 1 SD - Rahmah, Umatin; Dewi, Nurul Kemala; Mariana, Baiq (Darul Yasin Al Sys, 2023)
This research was conducted with the aim of improving learning outcomes through the problem-based learning (PBL) method assisted by picture card media in grade I elementary school students. The Problem Based Learning (PBL) method is a learning method that trains and develops the ability to solve an authentic problem of students' actual lives scientifically, which is arranged systematically and discovery is centered on the learner, so that it is expected to change the way students learn independently by improving student learning outcomes. This research is an action research (Class Piercing Research) which consists of three cycles. The conclusion in this study shows that the Problem Based Learning (PBL) method assisted by picture card media has been proven to improve student learning outcomes, namely 47.6% in cycle 1 and increased 71.4% in cycle 2 and in cycle 3 to 85,7%. Therefore, the Problem Based Learning (PBL) method assisted by picture card media is recommended to be applied in learning. The purpose of this study was to determine the use of the Problem Based Learning (PBL) method assisted by picture card media to improve learning outcomes. The study was conducted at SDN 15 Mataram with a class I sample of 21 students. From the data obtained, it is concluded that the use of the Problem Based Learning (PBL) method assisted by picture card media can improve learning outcomes.